IMPLEMENTATION OF FLIPPED CLASSROOM ON MATHEMATICS LEARNING AT SMP NEGERI 4 TANIMBAR SELATAN, DISTRICT OF TANIMBAR ISLANDS - Yospeh Watratan; Fransina Rangkoly; Mesak Ratuanik (Universitas Labuhanbatu, 2023)
The continuity of education held in 2020 is limited by the emergence of the spread of covid 19. This has made several countries set policies to impose lock down in order to prevent the spread of the corona virus. In Indonesia itself, a Large-Scale Social Restriction (PSBB) policy was implemented to suppress the spread of this virus. Because Indonesia is carrying out PSBB, all activities carried out outside the home must be stopped until this pandemic subsides. This study aims to determine the implementation of the Flipped Classroom model in online mathematics learning at SMP Negeri 4 Tanimbar Selatan. The type of research used in this research is qualitative research. namely exploratory descriptive research which means that researchers want to explore broadly about the causes and effects or things that affect the occurrence of something. The subjects in this study were class VII students of SMP Negeri 4 Tanimbar Selatan, totaling 18 students. The research instruments used in this study were: a) observation Observation aims to observe the effectiveness of student learning in learning mathematics online counting operations material by implementing the Flipped Classroom model, b) interview sheets are used to obtain information related to the effectiveness of learning mathematics material. operation of counting integers online by implementing the Flipped Classroom model c) Tests The test sheets in this study were given to students after being given mathematics lessons with learning videos that had been prepared by researchers to start learning in class. The results of this study indicate that applying the flipped classroom model can overcome problems in the face-to-face learning process and can improve student learning outcomes. This can be seen from the results of the final test of students who take part in the learning process because they feel happy when discussing in groups because they exchange ideas, help each other and freely ask for help from educators when experiencing difficulties.Keywords: Flipped Classroom, Math Learning.Â AbstrakPenelitian ini bertujuan untuk mengetahui implementasi model Flipped Classroom pada pembelajaran matematika secara daring di SMP Negeri 4 Tanimbar Selatan. Jenis penelitian yang digunakan dalam penelitian ini adalah penelitian kualitatif. yaitu penelitian deskriptif eksploratif yang berarti bahwa peneliti ingin menggali secara luas tentang sebab-akibat atau hal-hal yang mempengaruhi terjadinya sesuatu. Subjek dalam penelitian ini adalah siswa kelas VII SMP Negeri 4 Tanimbar Selatan yang berjumlahÂ 18 siswa. Instrumen penelitian yang digunakan dalam penelitian ini adalah: a) observasi Observasi bertujuan untuk mengamati efektivitas belajar siswa dalam pembelajaran matematika materi operasi hitung bilangan bulat secara daring dengan mengimplementasikan model Flipped Classroom, b) lembar wawancara digunakan untuk mendapatkan informasi yang berkaitan dengan efektivitas pembelajaran matematika materi operasi hitung bilangan bulat secara daring dengan mengimplementasikan model Flipped Classroom c) Tes Lembar tes dalam penelitian ini diberikan kepada siswasesudahdiberikan pembelajaranmatematika dengan video pembelajaran yang sudah disiapkan oleh peneliti untuk memulai pembelajaran di kelas. Hasil penelitian ini menunjukan bahwa bahwa dengan menerapkan model flipped classroom dapat mengatasi masalah terhadap proses pembelajaran tatap muka dan dapat meningkatkan hasil belajar siswa. Hal ini dilihat dari hasil tes akhir siswa yang mengikuti proses pembelajaran dikarenakan merasa senang saat berdiskusi dalam kelompok karena mereka bertukar pikiran, saling membantu dan secara bebas meminta bantuan dari pendidik saat mengalami kesulitan.Kata Kunci: Flipped Classroom, Pembelajaran MatematikaÂ